Pembangunan Kemaritiman dan Pesisir Studi Kasus: Analisis Kebijakan Jembatan Selat Sunda Peraturan Presiden Nomor 86 Tahun 2011 - Alim Bathoro (Jurnal Selat, 2016)
The process of development are two sides of the same coin, one side is the physical development and the other side is human development. However, in the development process, usually prefer the physical development, and less attention to human development. Therefore, people as objects, not subjects of development. The political authorities see development only in terms of economic benefits, the development of socio-political side ignored. Therefore, the development has a problem. Maritime development in the coastal areas and archipelago are also experiencing the same dilemma. In order to obtain an understanding of maritime development, this study will analyze the policy of the Sunda Strait bridge. Therefore, this study will analyze, who benefited from the Sunda Strait Bridge project, and who was defeated in the Sunda Strait Bridge project. If we read Peraturan Presiden (Perpres) No 86 Tahun 2011 related to the Sunda Strait Bridge, the actors had been found, they are government officials (local and central) and national enterprises. This research found that conflicts of interest between the central and local elite, has resulted in making the Sunda Strait bridge construction was delayed several times. Clearly, national enterprises seems to be the main actor in the local policy, both in Lampung and Banten. That is in local policies, local governments easily become part of the national enterprises interests Keywords : Policy, Actor, Elite, Government